Should tobacco and alcohol companies be allowed to influence Australia's National Drug Strategy? - Freeman, B.; MacKenzie, R.; Daube, Mike (2017)
Formation of Australia's National Drug Strategy (NDS) included an extensive consultation process that was open not only to community and public health stakeholders, but also to representatives of the tobacco and alcohol industries. Australia is bound by the World Health Organization Framework Convention on Tobacco Control, which requires governments to protect tobacco control measures from interference by the tobacco industry. NDS consultation submissions made by these conflicted industries are not publicly available for scrutiny. The NDS goals are at odds with the commercial agenda of industries that support regulatory stagnation, oppose and undermine effective action, ignore and distort evidence, and prioritise profits over health.